2004
DOI: 10.2977/prims/1145475447
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on a Class of Exact Solutions of the Navier–Stokes Equations and a Model for Turbulence

Abstract: In this paper we review some classes of exact solutions of the Navier-Stokes equations under a time-independent external straining flow, centering around the celebrated Burgers vortex. The objectives are (i) to clarify the relationship between them and (ii) to examine them as models of turbulence. Particularly we study the Lundgren spiral model for turbulence in the presence of azimuthal vorticity (that is, with axial velocity). The implication on linear stability of the Burgers vortex is briefly discussed. §1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In accordance with Lundgren, 4 the axial vorticity contributes to give Ϫ5/3 spectrum. The same approach was applied to the contribution of the azimuthal vorticity in Ohkitani 15 and it was shown that this vorticity gives Ϫ7/3 spectrum.…”
Section: Introductionmentioning
confidence: 86%
“…In accordance with Lundgren, 4 the axial vorticity contributes to give Ϫ5/3 spectrum. The same approach was applied to the contribution of the azimuthal vorticity in Ohkitani 15 and it was shown that this vorticity gives Ϫ7/3 spectrum.…”
Section: Introductionmentioning
confidence: 86%
“…Note that the solution for constant pressure gradient is similar to that for zero pressure gradient (17) because there will be a constant term in (5b), (6) and (7), and it can be expressed as the same polynomial in (8). It is interesting to note that more general solutions to (13) can be found by substituting additional terms which then resemble the following:…”
Section: Solutions For Pmentioning
confidence: 92%
“…They may help explain the issue of global smoothness in time [5]. Moreover, the solutions may be examined as models for turbulence [6].…”
Section: Introductionmentioning
confidence: 99%
“…Lundgren 17 has obtained a largetime asymptotic solution to the Navier-Stokes equations for the spiral layers of the axial vorticity subjected to an axisymmetric irrotational strain and shown that his spiral vortices exhibit the energy spectrum with a range of a Kolmogorov k −5/3 falloff ͑see also the works of Lundgren 24 and Gilbert 25 ͒. The spirals of the cross-axial vorticity in the axisymmetric straining flow have a k −7/3 spectrum at large wavenumbers, 26,27 and the energy dissipation for the spirals of the axial and the cross-axial vorticities can be of comparable order. 26 Recently, in their direct numerical simulation of isotropic turbulence, Kida and Miura 28 have found the existence of double spiral vortex layers with the dominant azimuthal compoment of vorticity, that is, the latter class of spirals.…”
Section: Introductionmentioning
confidence: 96%